Beta-2 Adrenergic Receptor Genotype Influences Power Output in Healthy Subjects - Kelley, Eli F; Johnson, Bruce D; Snyder, Eric M (Journal of strength and conditioning research, 2017)
Kelley, EF, Johnson, BD, and Snyder, EM. Beta-2 adrenergic receptor genotype influences power output in healthy subjects. J Strength Cond Res 31(8): 2053-2059, 2017-The purpose of this study was to determine the effects of ADRB2 genotypes on muscle function (absolute power and relative power) in healthy subjects. We performed genotyping of the ADRB2 (amino acid 16) and high-intensity, steady-state exercise on 77 healthy subjects (AA = 18, AG = 25, GG = 34). There were no differences between genotype groups in age, height, weight, or body mass index (BMI) (age = 28.9 ± 5.7 years, 27.9 ± 5.7 years, 29.2 ± 5.9 years, height = 170.7 ± 8.6 cm, 174.9 ± 8.7 cm, 173.4 ± 9.6 cm, weight = 68.5 ± 13.0 kg, 75.0 ± 12.9 kg, 74.4 ± 12.9 kg, and BMI = 23.4 ± 3.9, 24.4 ± 2.9, 24.7 ± 3.4, for AA, AG, and GG, respectively). The genotype groups differed significantly in watts, and watts/V[Combining Dot Above]O2 with heavy exercise (watts = 186.3 ± 54.6, 237.8 ± 54.4, 219.4 ± 79.5, watts/V[Combining Dot Above]O2 = 0.08 ± 0.006, 0.09 ± 0.005, 0.08 ± 0.006). There was a trend toward significance (p = 0.058) for W·kg (2.7 ± 0.4, 3.2 ± 0.5, 2.9 ± 0.8, for AA, AG, and GG, respectively). These data suggest that genetic variation of the ADRB2 may influence relative strength in healthy subjects and may become an important genetic determinant of muscular strength and functional capacity in patients with diseases that result in a loss of muscle strength.